Comparison of hemodynamic alterations and post-operative profile of sevoflurane and propofol during laparoscopic cholecystectomies - Swarup Dutta; Tirtha Ratan Ghosh; Goswami, Debarati; Subrata Mondal; Somnath Dey; Debasish Saha (Asian Journal of Medical Sciences, 2023)
Background: Modern laparoscopic surgeries with insufflation of gas into peritoneal cavity are gold standard treatment for cholelithiasis. Propofol, a GABA receptor positive allosteric modulator and Sevoflurane, an inhalational anesthetic are used for maintenance of general anesthesia. In laparoscopy, significant hemodynamic changes occur. Searching in field of anesthesia is going on for anesthetic agent for better recovery. Aims and Objectives: Objective of the study is to compare sevoflurane with propofol for intraoperative hemodynamic changes and post-operative recovery profile of patient’s undergone laparoscopic cholecystectomies under general anesthesia. Secondary objective is to compare post-operative complications. Materials and Methods: A prospective, randomized, single-blinded, and comparative study done after permission from the institutional ethical committee and informed consent from patients. Total 84 patients of 20–50 years age of either sex were scheduled for laparoscopic cholecystectomy, divided in two equal groups – Group P, induced with propofol and anesthesia was maintained with propofol (100–120 μg/kg/min), nitrous oxide and oxygen and Group S induced with propofol and anesthesia was maintained using sevoflurane (1–2%), nitrous oxide, and oxygen. Results: We found that time for eye opening was 9±1.21 min in Group P and 8±1.34 min in Group S. Time for following verbal command was 10±1.20 min in Group P and 9±1.32 min in Group S. Time for speaking name by patient was 11±1.20 min in Group P and 10±1.34 min in Group S. Difference between two groups regarding eye opening, following verbal command, and time to speak own name are highly significant with P<0.001 which proves that eye opening, following verbal command and time for speaking name by patient were significantly shorter in sevoflurane group. Time to achieve modified aldrete score >8 was 14±1.30 min in Group P and 13±1.37 min in Group S. Difference between two groups is also highly significant with P<0.001 which proves that time to achieve modified aldrete score>8 were significantly shorter in sevoflurane group. Conclusion: From our study, maintenance of general anesthesia with sevoflurane is associated with faster recovery from anesthesia.